DEVELOPMENT OF ORGANIZATIONAL FORMS OF TRAINING OF THE TEACHER OF INFORMATICS IN THE CONDITIONS OF EXPANSION OF TASKS OF HIS PROFESSIONAL ACTIVITY - Magomedov, R.M. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
In article is considered ways of improvement of education due to use of modern organizational forms of education. The author notes that the new understanding society of values and is more whole than education, value of educational results and cause the directions of modernization of education and if modern educational results are regarded as of paramount importance, then it is possible to achieve them only in the course of new according to contents and in organizational forms of educational activity. Didactic opportunities of use of modern organizational forms are given in article by preparation and retraining of future teachers of informatics. Need of granting to the teacher of informatics of ample opportunities for the choice of organizational forms, innovative methods, new tutorials for professional improvement is noted. That is, is urgent, according to the author, search of the methodological and didactic bases for systematization of organizational forms of education of future teachers of informatics, development already known and development of new forms of education, designing on their basis of pedagogical technologies. Therefore, it is noted, need of the solution of a complex of tasks of development of organizational forms of training of future teachers of informatics in the conditions of expansion of tasks of his professional activity.